A new sand and gravel map for the UK Continental Shelf to support sustainable planning. (June 2016) - Bide, Tom; Balson, Peter; Mankelow, Joseph; Selby, Ian
Abstract: The planning framework for the UK Continental Shelf (UKCS) is undergoing significant change. An integrated plan-led process, similar to that undertaken onshore, is now being applied offshore. It is vital that marine mineral resources are adequately considered in this process. In order to facilitate this, the first ever sand and gravel mineral resources map of the entire UKCS has been created. Offshore resources have been defined by integrating geological mapping data and the British Geological Survey's extensive collection of core, sea bed sample and geophysical records. A spatial model has been developed that highlights the location and likely composition of sand and gravel deposits with the results undergoing geological review to ensure different sea-bed features have been adequately represented. Results are presented as a series of four maps covering the entire UKCS. With increasing pressure on marine space it is important to balance the competing demands and needs from different use sectors. Identification of the distribution of sand and gravel resources at a national scale and presentation in a consistent fashion allows planners to adequately consider minerals in the planning process and permits more effective and sustainable sea-use management strategies to be developed. Highlights: The first map depicting the marine sand and gravel resources of the UK has been developed. Spatial data is needed for marine spatial planning as required by EU regulations. This dataset is being used to ensure minerals are protected and considered in the planning process.